“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction

L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)
Organisé par l’Observatoire interdisciplinaire de création et de recherche en musique et le Centre des musiciens du monde, le colloque Femmes musiciennes du monde visait à explorer les parcours professionnels de musiciennes migrantes. Des conférences et tables rondes ont fait intervenir des chercheuses en sociologie, anthropologie, musicologie et ethnomusicologie ainsi que des musiciennes ayant immigré à Montréal. De la combinaison de ces savoirs scientifique et expérientiel s’est dégagée une série de difficultés et défis récurrents pour les femmes en musique : invisibilisation du travail, différenciations et discriminations genrées dans un milieu majoritairement masculin, enjeux liés au corps féminin ainsi qu’à la mobilité géographique. Or, il s’est aussi affirmé des spécificités d’expériences, de profils et de stratégies selon les parcours migratoires. Cette note de terrain synthétise les principaux constats, mais aussi les limites des discussions de ce colloque avant d’identifier quelques-uns des nombreux efforts qu’il reste à déployer pour mieux comprendre les réalités de telles artistes.
Keywords: 2000 à aujourd'hui; 2020-2029; DIG; agentivité; anthropologie; approches et analyses; arts; corps; discipline; discriminations; femmes* artistes; femmes* immigrantes; femmes* musiciennes; intersectionnalité; invisibilité historique; musique; périodes historiques; racisme; ressource en ligne; savoir expérientiel; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie